2017
DOI: 10.1088/1741-4326/aa6f2b
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous, edge localized ion heating during non-solenoidal plasma startup and sustainment in a low aspect ratio tokamak

Abstract: There was a publishing error introduced during the processing of figure 9. It should appear as shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The relationship between continued (and even improved) current drive and the increase in magnetic fluctuation activity at high frequency inside the plasma edge is a subject of ongoing investigation, and may inform the current drive physics of LHI. Past work has shown that high-frequency activity during LFS LHI is well correlated with reconnection-driven ion heating [36]. While this is a new observation for LHI, note that a similar observation was made in plasmas sustained by CHI in HIT-II that exhibited flux amplification [37].…”
Section: Discussionsupporting
confidence: 60%
“…The relationship between continued (and even improved) current drive and the increase in magnetic fluctuation activity at high frequency inside the plasma edge is a subject of ongoing investigation, and may inform the current drive physics of LHI. Past work has shown that high-frequency activity during LFS LHI is well correlated with reconnection-driven ion heating [36]. While this is a new observation for LHI, note that a similar observation was made in plasmas sustained by CHI in HIT-II that exhibited flux amplification [37].…”
Section: Discussionsupporting
confidence: 60%
“…Passive impurity Doppler spectroscopy indicated that the ion temperatures in LHI-initiated discharges was anomalously high, in that routinely exceeds the central [20]. Experiments confirmed that this anomalous ion heating is driven by strong magnetic reconnection activity present during LHI.…”
Section: Advancing Lhi Physics Understandingmentioning
confidence: 89%
“…The physical mechanisms leading to LHI current drive generate strong MHD activity. Nonlinear, 3D resistive MHD NIMROD simulations of LHI startup have provided insight into dynamical processes observed in experiment and simulation [19], and spurred experimental investigations into MHD activity [13] and reconnection [20] during LHI.…”
Section: Advancing Lhi Physics Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics improve MHD stability. Recent work has shown LHI also fortuitously provides magnetic-reconnection-driven ion heating that increases the total plasma pressure without a separate ion heating source [17]. Impurity ion temperature measurements indicate is typically 1-3 times during LHI.…”
mentioning
confidence: 99%